Visual vertical neglect in acquired brain injury: a systematic review - Moretta, Pasquale; Cavallo, Nicola Davide; Fonzo, Eleonora; Maiorino, Antonio; Ferrante, Cesario; Ambrosino, Pasquale; Femiano, Cinzia; Santangelo, Gabriella; Marcuccio, Laura (Frontiers in Psychology, 2024)
Vertical neglect represents a visuospatial deficit occurring as a possible consequence of acquired brain injury (ABI). Differently from unilateral spatial neglect on horizontal space, vertical neglect is poorly studied in the literature and rarely assessed in clinical practice. In the available studies, the terms “radial,” “vertical,” and “altitudinal” neglect are often used interchangeably, although they do not describe the same spatial dimension. “Altitudinal” and “vertical” refer to the sagittal plane, whereas “radial” refers to the transverse plane. The term “vertical” is sometimes used interchangeably with respect to both axes. The aim of this systematic review was to identify the main characteristics of vertical neglect after ABI, the diagnostic tools used, and the treatment options. We also proposed a clarification of the manifestations and characteristics of vertical and radial neglect. The 23 articles reviewed, showed that the vertical neglect occurred more frequently on the lower space than on the upper space, that its presence was associated with horizontal neglect, and that it could also occur with compromise of the radial space, with the near radial being more common. The most frequent etiology associated with vertical neglect is vascular, particularly ischaemic. The lesions side are very heterogeneous and include both cortical and subcortical areas and all lobes, although the temporal lobe is most affected. With regard to the assessment tools, paper and pencil tasks are the most commonly used diagnostic tools to identify vertical neglect, although in recent years the use of computer-based tasks increased. Taken together, our results suggest that vertical neglect may be underestimated in patients with right hemisphere lesions and should always be assessed, especially in cases where the patient shows signs of horizontal neglect. The clinical assessment of vertical neglect is very important since it can lead to important functional limitations in everyday life, such as poor wheelchair handling, stumbling over unnoticed obstacles located below (or above), walking down stairs, taking off shoes.